2019
DOI: 10.2486/indhealth.2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the International Classification of High-resolution Computed Tomography for occupational and environmental respiratory diseases with the International Labor Organization International Classification of Radiographs of Pneumoconiosis

Abstract: The International Classification of High-resolution Computed Tomography for Occupational and Environmental Respiratory Diseases (ICOERD) has been developed for screening and diagnosis of occupational lung diseases. We evaluated the association of icoerd with the International Labor Organization (ILO) classification and respiratory functions in pneumoconiosis. Chest x-rays of patients with pneumoconiosis were classified with ilo and icoerd using hrct, irregular opacity, pleural pathology, and emphysema was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…This might be attributed to the moderate fibrosis (maximum score was 6 of theoretically achievable 18 points) in all cases. Likewise, Şener et al [33] described only a weak negative correlation between FEV 1 and FVC decrease with the increase of small opacitiy grades in HRCT; however, the D LCO was not investigated by these authors. Barnikel et al [34] showed a decrease of FVC and D LCO in 56 asbestos exposed subjects, particularly significant in cases with fibrotic phenotype in HRCT.…”
Section: Discussionmentioning
confidence: 91%
“…This might be attributed to the moderate fibrosis (maximum score was 6 of theoretically achievable 18 points) in all cases. Likewise, Şener et al [33] described only a weak negative correlation between FEV 1 and FVC decrease with the increase of small opacitiy grades in HRCT; however, the D LCO was not investigated by these authors. Barnikel et al [34] showed a decrease of FVC and D LCO in 56 asbestos exposed subjects, particularly significant in cases with fibrotic phenotype in HRCT.…”
Section: Discussionmentioning
confidence: 91%
“…However, these methods cannot detect the disease until it has significantly progressed [ 29 ]. Although it has been reported that CXR cannot reliably detect occupational lung diseases [ 30 ], it is still recommended in the diagnosis of silicosis by the International Labour Organisation (ILO) Classification System [ 31 ]. Poor-quality chest radiographs, physicians' inability to recognize the disease, and the differential latency of various types of occupational lung diseases make it difficult to detect and estimate the burden of silicosis [ 32 , 33 ].…”
Section: Clear Causes and Unresolved Mechanisms Of Silicosismentioning
confidence: 99%
“…[ 26 ] The use of digital standard images makes telemedicine and remote counseling possible, and provides ample opportunity for the accurate and timely diagnosis of pneumoconiosis. While high-resolution computed tomography (HRCT) is more sensitive to the detection of early signs than chest x-rays are, [ 27 ] the International Classification of HRCT for Occupational and Environmental Respiratory Diseases (ICOERD) has developed and recommended a list of diagnoses for occupational and environmental related lung diseases. [ 28 ] ILO classification remains valid for practical reasons, because there is currently no global standard.…”
Section: Diagnosis Of Pneumoconiosismentioning
confidence: 99%
“…[ 28 ] ILO classification remains valid for practical reasons, because there is currently no global standard. [ 8 , 27 ] Because imaging techniques cannot assess the functional status of the patient, pulmonary function tests (PFT) are used as a supplementary method of the evaluation of the disease. PFT can be used to assess dyspnea, distinguish between obstructive and restrictive diseases, and assess disease severity.…”
Section: Diagnosis Of Pneumoconiosismentioning
confidence: 99%
See 1 more Smart Citation